Herding Behavior in The Asean Stock Market During The Covid-19 Pandemic - Rahmayanti, Dewi; Santi, Fitri; Altin, Darus; Ridwan, Muhammad Qomaruddin; Wan Mohd Nazdrol (Universitas Muhammadiyah Surakarta, 2023)
This study aims to detect indications of herding behavior that occurred in the ASEAN capital market throughout the COVID-19 pandemic. The research spanned from December 31, 2019, to June 30, 2021, encompassing the duration of the COVID-19 pandemic. This research used panel regression and rolling window regression methods on the dependent variable of Cross-Sectional Absolute Deviation (CSAD) to detect indications of herding behavior. This research also employed daily stock return data for all companies on several stock exchanges in five ASEAN countries. The panel regression model was then utilized in the analysis. The panel regression results demonstrated the absence of herding behavior on the stock exchanges in ASEAN. This was evident as the Rm2 coefficient consistently revealed a significant positive sign throughout the entire observation period. However, upon rechecking through rolling window regression, it was uncovered that, at some times, herding did occur on the ASEAN stock exchange during the COVID-19 pandemic. Furthermore, the government’s policy response by limiting short selling could reduce herding on the stock market. Simultaneously, the government’s policy response to the COVID-19 epidemic, proxied by the Stringency Index, apparently heightened investor anxiety and promoted herding behavior. Lastly, the heightened levels of anxiety and volatility experienced during the pandemic (variable IVI) led to a rise in herd behavior among the stock markets of ASEAN countries.